Ketika Hidup dan Kerja Seimbang Sebagai Kunci Optimalisasi Kinerja Karyawan di PT. X - Putri Cahya Rahma Dewi; Netty Dyan Prastika; Nanik Handayani; Frida Zakiyya Harasuna (Jayapangus Press, 2026)
Work-life balance has become an important issue in human resource management as it relates to employees’ ability to balance work demands and personal life. An imbalance between these roles may lead to stress, role conflict, and decreased work performance. Therefore, this study aimed to examine the relationship between work-life balance and employee performance at PT X, a nationally scaled fertilizer industry company. This study employed a quantitative approach with a correlational design. The population consisted of all employees of PT X, with a sample of 131 employees selected using probability sampling through simple random sampling. Data were collected using Likert-scale instruments, including an employee performance scale and a work-life balance scale. The employee performance scale showed a reliability coefficient of 0.925, while the work-life balance scale demonstrated a reliability coefficient of 0.928. Data analysis was conducted using Pearson Product Moment correlation after fulfilling the assumptions of normality and linearity. The results indicated a positive and significant relationship between work-life balance and employee performance (r = 0.534; p < 0.05). This finding suggests that employees with higher levels of work-life balance tend to demonstrate better performance. A balance in time, involvement, and satisfaction between work and personal life contributes to emotional stability, improved focus, and more productive work behaviors. In conclusion, work-life balance is a crucial psychological factor that supports employee performance improvement. Therefore, organizations are encouraged to implement work policies that promote work-life balance, such as flexible work arrangements and employee well-being programs, to achieve sustainable performance enhancement.